Comparisons between different blood pressure measurement techniques in patients with chronic kidney disease - Shahrokh Ezzatzadegan Jahromi; Ghasem Haghighi; Jamshid Roozbeh; Vahid Ebrahimi (The Korean Society of Nephrology, 2019)
Background : Automated office blood pressure (AOBP) machines measure blood pressure (BP) multiple times over a brief period. We aimed to compare the results of manual office blood pressure (MOBP) and AOBP methods with ambulatory BP monitoring (ABPM) in patients with chronic kidney disease (CKD). Methods : This study was performed on 64 patients with CKD (stages 3-4). A nurse manually measured the BP on both arms using a mercury sphygmomanometer, followed by AOBP of the arm with the higher BP and then ABPM. Mean BP readings were compared by paired t test and Bland-Altman graphs. Results : The mean ± standard deviation (SD) age of participants was 59.3 ± 13.6. The mean ± SD awake systolic BP obtained by ABPM was 140.2 ± 19.0 mmHg, which was lower than the MOBP and AOBP methods (156.6 ± 17.8 and 148.8 ± 18.6 mmHg, respectively; P < 0.001). The mean ± SD awake diastolic BP was 78.6 ± 13.2 mmHg by ABPM which was lower than the MOBP and AOBP methods (88.9 ± 13.2 and 84.1 ± 14.0 mmHg, respectively; P < 0.001). Using Bland-Altman graphs, MOBP systolic BP readings showed a bias of 16.4 mmHg, while AOBP measurements indicated a bias of 8.6 mmHg compared with ABPM. Conclusion : AOBP methods may be more reliable than MOBP methods for determining BP in patients with CKD. However, the significantly higher mean BPs recorded by AOBP method suggested that AOBPs may not be as accurate as ABPM in patients with CKD.